2022
DOI: 10.1111/aos.15140
|View full text |Cite
|
Sign up to set email alerts
|

Mouse microphthalmia‐associated transcription factor (Mitf) mutations affect the structure of the retinal vasculature

Abstract: Purpose: Mice carrying pathogenic variants in the microphthalmia transcription factor (Mitf) gene show structural and functional changes in the retina and retinal pigment epithelium. The purpose of this study was to assess the vascular changes in Mitf mice carrying pathogenic variants by determining their retinal vessel diameter. Methods: Mice examined in this study were: B6-Mitf mi-vga9/+ (n = 6), B6-Mitf mi-enu22(398) /Mitf mi-enu22(398) (n = 6) and C57BL/6J wild type mice (n = 6), all 3 months old. Fundus i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“… 34 – 38 One gene of particular interest, Mitf , is expressed solely in the RPE and plays a crucial role in RPE function. 39 42 Loss of this gene has been connected to the loss of RPE pigmentation and the loss of RPE phenotype, thus supporting the results seen from H&E staining and TEM. 43 , 44 RT-qPCR also showed Mitf gene expression in 12 month p;d LCHADD RPE/sclera was 60% lower compared to WT, confirming RNA-sequencing results ( Fig.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“… 34 – 38 One gene of particular interest, Mitf , is expressed solely in the RPE and plays a crucial role in RPE function. 39 42 Loss of this gene has been connected to the loss of RPE pigmentation and the loss of RPE phenotype, thus supporting the results seen from H&E staining and TEM. 43 , 44 RT-qPCR also showed Mitf gene expression in 12 month p;d LCHADD RPE/sclera was 60% lower compared to WT, confirming RNA-sequencing results ( Fig.…”
Section: Resultssupporting
confidence: 73%
“…The downregulation of Mitf further supports RPE dysfunction and loss of boundary formation as this gene has been shown to be crucial in RPE development and differentiation and transepithelial transport. 41,42 Overall, the LCHADD mouse chorioretinopathy mirrors what has been observed in patients with LCHADD and provides a useful model to study the molecular mechanisms involved with the chorioretinopathy.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The retinal circulation is a true end artery system, with all the blood from the retinal arteries passing via the capillary beds to retinal venules and the central retinal vein. With fundus imaging, the retinal circulation can be easily viewed and examined, and structural and functional parameters such as vessel diameter ( Pedersen et al, 2005 ; Daníelsson et al, 2022 ; García-Llorca et al, 2023 ) and alterations in blood flow ( Marino et al, 2021 ) can be readily measured. The retinal vasculature tends to maintain a steady level of blood flow and oxygenation in the retina, by intrinsic autoregulation ( Riva et al, 1981 ; Dumskyj et al, 1996 ) in response to changes in perfusion pressure, intraocular pressure, or blood gasses (la Cour et al, 2000 ), but the myogenic response, considered to be the basis of autoregulation, is held to be intrinsic to vascular smooth muscle cells ( Davis and Hill, 1999 ).…”
Section: Carbonic Anhydrase and The Retinal Vasculaturementioning
confidence: 99%
“…Mitf -deficient mice show pathological features of albinism, microphthalmia, deafness, hypopigmentation, and retinal degeneration [21,23,25,34]. Recently, it was demonstrated that Mitf mutant and control mice have considerably different retinal vessel diameters and differences in the number of retinal vessels [35]. Loss of pigmentation, smaller eyes, failure of secondary bone resorption, fewer mast cells, and early-onset hearing loss are all or part of the abnormalities present in mice with mutations at the microphthalmia (mi) locus [34,[36][37][38].…”
Section: Introductionmentioning
confidence: 99%